Effects of the sodium‐glucose cotransporter 2 inhibitor dapagliflozin on fluid distribution: A comparison study with furosemide and tolvaptan. Issue 9 (2nd May 2019) - Ohara, Ken; Masuda, Takahiro; Murakami, Takuya; Imai, Toshimi; Yoshizawa, Hiromichi; Nakagawa, Saki; Okada, Mari; Miki, Atsushi; Myoga, Akihiro; Sugase, Taro; Sekiguchi, Chuji; Miyazawa, Yasuharu; et al.
ABSTRACT: Aim: Sodium‐glucose cotransporter 2 (SGLT2) inhibitors are an antihyperglycemic drug with diuretic properties. We recently reported that an SGLT2 inhibitor ameliorated extracellular fluid expansion with a transient increase in urinary Na + excretion. However, the effects of SGLT2 inhibitors on fluid distribution in comparison to conventional diuretics remain unclear. Methods: Forty chronic kidney disease patients with fluid retention (average estimated glomerular filtration rate 29.2 ± 3.2 mL/min per 1.73 m 2 ) were divided into the SGLT2 inhibitor dapagliflozin (DAPA), loop diuretic furosemide (FR) and vasopressin V2 receptor antagonist tolvaptan (TLV). The body fluid volume was measured on days 0 and 7 using a bioimpedance analysis device. Results: In all three groups, body weight was significantly and similarly decreased, and urine volume numerically increased for 7 days. Bioimpedance analysis showed that the changes in intracellular water were similar, but that there were significant changes in the extracellular water (ECW) (DAPA −8.4 ± 1.7, FR −12.5 ± 1.3, TLV −7.4 ± 1.5%, P  = 0.048). As a result, the change in the ratio of ECW to total body water in the DAPA group was significantly smaller than that in the FR group, but numerically larger than that in the TLV group (DAPA −1.5 ± 0.5, FR −3.6 ± 0.5, TLV −0.5 ± 0.4%, P  < 0.001). Conclusion: Sodium‐glucose cotransporter 2 inhibitor DAPA predominantly decreased the ECW with a mild increase in urine volume, but the change in the ECW/total body water was smaller than that in patients treated with FR, and larger than that in patients treated with TLV, suggesting that the effects of SGLT2 inhibitors on fluid distribution may differ from those of conventional diuretics. SUMMARY AT A GLANCE: This non‐randomized study examines the influence of a sodium‐glucose cotransporter 2 (SGLT2) inhibitor on fluid distribution in patients compared to furosemide and tolvaptan. It was found that dapagliflozin predominantly decreased the extracellular water with a mild increase in urine volume, and the magnitude was smaller than furosemide, but larger than tolvaptan, suggesting that the effects of SGLT2 inhibitors on fluid distribution may differ from those of conventional diuretics.